ChemInform Abstract: α‐Fluorohydrazones as Useful Precursors in Nucleophilic Substitutions. Issue 46 (24th October 2013) - Yunoki, Ryota; Yajima, Atsushi; Taniguchi, Tsuyoshi; Ishibashi, Hiroyuki
Abstract C—F bonds in title compounds such as (I), (IV), and (XII) can be easily substituted with a wide range of nucleophiles in the presence of a mild base.